Penyebab Kelangkaan Minyak Goreng Di Indonesia: Panic buying, Praktik Kartel, Penimbunan Minyak Goreng - Anisa, Cindy; Surbakti, Rizky Damar Wicaksono; Mahardika. P, Thaniea (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
The cooking oil shortage problem that has occurred in Indonesia since late 2021 until mid-2022 has had a significant impact on the social and economic aspects of the community. As one of the important staples for the community, the availability of cooking oil is influenced by global market conditions as well as domestic policies. This study aims to identify the causes of the cooking oil shortage in Indonesia and evaluate the effectiveness of the handling measures taken by the government. The main causes identified are panic buying by consumers, alleged hoarding of oil by certain parties, cartel practices in the cooking oil sector, and irregular distribution of oil. The rising demand for crude palm oil (CPO) in international markets, such as India and China, has also worsened the situation by increasing the price of raw materials globally. On the other hand, the government's efforts through the policy of setting the Highest Retail Price (HET) for bulk and packaged cooking oil failed to address the scarcity, due to lack of distribution supervision. As a result, cooking oil stocks in local markets became scarce, triggering consumer panic, creating a long purchase queue, and uncontrolled price hikes. In addition, the practice of market manipulation by some business actors and the alleged existence of a cooking oil mafia exacerbated the situation, creating public distrust of the policies implemented. This research uses a descriptive qualitative approach, with data obtained from literature studies and analysis of official websites. The results show that the scarcity of cooking oil is not only caused by external factors such as global trade, but also by weaknesses in the domestic system including distribution, supervision, and inconsistent policies. As a solution, it is suggested that there should be cooperation between the government, business actors, and regulatory agencies to improve distribution transparency, address cartel practices and hoarding of cooking oil, and strengthen regulations related to domestic cooking oil production and distribution. With the implementation of integrated policies, it is expected that the stability of cooking oil supply and prices can be achieved in accordance with the wishes of the community, so that the Indonesian people, especially the lower middle class, are no longer burdened by price fluctuations and have equal access to cooking oil.